2015
DOI: 10.1590/0103-6440201300212
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatment of Pre-hydrolyzed Silane Increases Adhesion of Phosphate Monomer-based Resin Cement to Glass Ceramic

Abstract: This study evaluated the influence of different forms of heat treatment on a pre-hydrolyzed silane to improve the adhesion of phosphate monomer-based (MDP) resin cement to glass ceramic. Resin and feldspathic ceramic blocks (n=48, n=6 for bond test, n=2 for microscopy) were randomly divided into 6 groups and subject to surface treatments: G1: Hydrofluoric acid (HF) 9.6% for 20 s + Silane + MDP resin cement (Panavia F); G2: HF 9.6% for 20 s + Silane + Heat Treatment (oven) + Panavia F; G3: Silane + Heat Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 14 publications
(34 reference statements)
2
25
0
1
Order By: Relevance
“…The hydroxyl group (-OH) of MDP monomer can chemically react with the hydroxyl group of zirconia oxides [10]. That promotes a stable chemical bond resistant to hydrolytic degradation [18], which, however, may be weakened after thermal cycling [10] but still effective to promote zirconia bonding [19,20]. In the 30 s no-cycled groups (30SRc/ no-C, 30SUaRc/no-C and 30UaRc/no-C), the use of universal adhesive promoted higher bond strength values than silane.…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyl group (-OH) of MDP monomer can chemically react with the hydroxyl group of zirconia oxides [10]. That promotes a stable chemical bond resistant to hydrolytic degradation [18], which, however, may be weakened after thermal cycling [10] but still effective to promote zirconia bonding [19,20]. In the 30 s no-cycled groups (30SRc/ no-C, 30SUaRc/no-C and 30UaRc/no-C), the use of universal adhesive promoted higher bond strength values than silane.…”
Section: Discussionmentioning
confidence: 99%
“…De Carvalho et al [21] heated a pre-hydrolyzed silane containing MDP (Clearfil Ceramic Primer) in an oven at 100 °C for 2 min or applied hot air at 50 °C for 1 min. The results of that study indicated that both treatments were effective in increasing the bond strength values between the feldspathic ceramic and resin cement.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest bond strength was found for a pre-hydrolyzed silane containing phosphate monomer-based MDP. Its manufacturer does not recommend hydrofluoric acid etching, because MDP monomer should be able bond to ceramic without acid etching treatment by very strong bonds to SiO 2 based ceramics and metal oxides [21]. Without the microporosities promoted by acid etching, the silane containing phosphate monomer-based MDP yielded approximately 19% (for heat treatment) and 29% (no heating) lower bond strength than those silanes applied to acid etched ceramic.…”
Section: Discussionmentioning
confidence: 99%
“…This is a monomer containing reactive organic group and monovalent hydrolysable group that form siloxane bonds between the inorganic phase of the ceramic and the organic phase of the applied resin cement [2][3][4][5]. The chemical bond promoted by the silane coupling agent is the main mechanism behind feldspathic ceramic adhesion to resin cements [6][7]. Furthermore, silane increases the surface energy of ceramic substrates and improves cement wetting, optimizing the microscopic interaction between cement and ceramic [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical bond promoted by the silane coupling agent is the main mechanism behind feldspathic ceramic adhesion to resin cements [6][7]. Furthermore, silane increases the surface energy of ceramic substrates and improves cement wetting, optimizing the microscopic interaction between cement and ceramic [6][7].…”
Section: Introductionmentioning
confidence: 99%